IMPROVING TOURISM ACCESS THROUGH WEBSITE-BASED DIGITAL TECHNOLOGY UTILIZATION - Hartatik Hartatik; Ditya Galassepda Putri (International Journal of Engagement and Empowerment, 2023)
The tourism industry is a sector that has great potential in driving the economy of a region. To optimize this potential, the use of technology can be an effective alternative. Therefore, this community service aims to develop a technology-based tourism system through an e-tourism website at the Regency-level Tourism, Youth and Sports Office. In the early stages, an analysis of the existing tourism system was carried out and identification of user needs. Then, technology-based system development is carried out through the creation of an e-tourism website that displays information about tourist objects, travel routes, and other supporting services. The use of this technology is expected to provide convenience for tourists in accessing information about tourism at the district level. In addition, the development of e-tourism is also expected to expand the Madiun Regency tourism market by accommodating the needs of tourists who are more inclined to use digital technology in planning their tour trips. Through this community service, it is hoped that the Regency Tourism, Youth and Sports Office can increase the competitiveness of the tourism industry through the use of more modern and effective technology